Isolation and identification of serotonin compound from banana hump: a reproductive stimulant for tiger shrimp Penaeus monodon broodstock enhancement - Andi Parenrengi; Emma Suryati; Rachman Syah; Andi Tenriulo; Samuel Lante; Elmi Nurhaidah Zainuddin; Ratu Siti Aliah; Nuril Farizah; Agus Nawang; Sulaeman Sulaeman; Makmur Makmur; Rosmiati Rosmiati; et al. (PeerJ)
Background The banana plant is claimed to contain a serotonin compound that has the potential to stimulate and improve the reproductive performance of crustacean species. This study aimed to isolate and characterize the serotonin compound from the banana hump and its application to enhance the reproductive performance of tiger shrimp broodstock. Methods Banana hump as a part of the plant was extracted by using the maceration technique. The chemical structure of the serotonin compound was identified and characterized based on spectroscopic data, including high-performance liquid chromatography (HPLC), ultraviolet-visible (UV-Vis) spectroscopy, and infrared (IR) spectroscopy, and a comparison was made with the standard compound and the literature. The extract herb in a dose of 50 µg/g body weight was injected into the tiger shrimp broodstock in four-time administrations. During 2 months of broodstock gonadal maturation, the parameters of molting, reproduction, and gene expression related to reproduction were observed. Results Based on the chemical structure analysis, the stimulant component of the banana hump was identified as a serotonin compound (5-hydroxytryptamine) at a concentration of 0.7% of dry weight. The number of spawned broodstock was higher in the serotonin extract treatment (60%) than in the control treatment (40%), and the broodstock injected serotonin spawned up to the second re-maturation. In contrast, no re-maturation was obtained in the control treatment. The egg number was significantly higher using the serotonin extract (286,550 ± 46,402 eggs) than the control shrimp (148,585 ± 23,647 eggs), in which the serotonin extract treatment showed a comparatively larger egg diameter number. The higher expression of the genes related to female and male reproduction was observed in the tiger shrimp injected with serotonin extract than in the control treatment.